Magnetic diagnostics for torsatron U-2M - Pashnev, V.K.; Petrushenya, A.A.; Sorokovoy, E.L.; Krasnyj, V.V. (Вопросы атомной науки и техники, 2011)
The features of application of magnetic diagnostics in torsatron U-2M are described. The methods to account for the influence of the metal environment and induced magnetic fields on the results of magnetic measurements are presented. During the experimental program on torsatron U-2M with help of magnetic diagnostics, the most important characteristics of the plasma, such as the value of the plasma energy content, the energy confinement time, the power inputted in the plasma, the value of Pfirsch-Schluter currents, the presence of magnetic islands, the shift of magnetic surfaces, the structure of MHD instabilities will be determined